THU0265 THYMIC STROMAL LYMPHOPOIETIN (TSLP) AS A BIOMARKER OF PRIMARY SJÖGREN'S SYNDROME (PSS) AND RELATED LYMPHOMA: VALIDATION IN INDEPENDENT COHORTS. (2nd June 2020) - Gandolfo, S.; Fabro, C.; Colafrancesco, S.; Carubbi, F.; Ferro, F.; Bartoloni Bocci, E.; Kapsogeorgou, E.; Goules, A.; Quartuccio, L.; Priori, R.; Alunno, A.; Valesini, G.; et al.
Abstract : Background: Thymic stromal lymphopoietin (TSLP) has been implicated in primary Sjögren's syndrome (pSS) and related B-cell lymphoproliferation/lymphoma (NHL) by tissue studies on salivary glands (SG) (1). It resulted significantly higher in the serum of pSS patients compared to non-pSS sicca and to healthy subjects, with the highest levels found in NHL. Objectives: The purpose of this work was to confirm that serum TSLP is elevated in pSS by the study of independent cohorts. Methods: Serum TSLP levels were measured by ELISA in 91 pSS patients (F=86, 94.5%; mean age 57.2 years, 25-80) from the Udine cohort (cohort 1, UD), Italy. One additional multicentre cohort (cohort 2) from the Italian SS Study Group (GRISS) was studied, including 125 pSS patients from the Universities of Roma (RO), L'Aquila (L'AQ), Pisa (PI) and Perugia (PG). pSS patients with active NHL (n=12 in cohort 1; n=1 in cohort 2) were excluded from comparative analyses to avoid bias. Secondly, additional serum samples from pSS-related NHL in stable and complete remission, from both cohort 1 and 2, were analysed in a separate subgroup (n = 12). Thirdly, a preliminary evaluation of serum TSLP was performed in pSS patients from a different geographical area (University of Athens, Greece; cohort 3). Results: Cohort 2 included 125 pSS patients (F=114, 91.2%; mean age 58.1 years, 23-84): 124 benign, 1 with NHL. In this cohort, serum TSLP levels were confirmed to be high (mean 30.26 pg/mL, 0.41-95.21) and comparable to cohort 1 (mean 33.81 pg/mL, 0-140.8; p=ns). No difference was found by the separate analysis of pSS from each single Centres (RO n=49, mean 33.21, 1.4-95.21; L'AQ n=34, mean 38.6, 16.31-85.11; PI n=28, mean 20.23, 0.41-56.67; PG n=13, mean 19.39, 1.03-68.38; p=ns), and vs cohort 1 (p=ns). The only patient in cohort 2 with NHL showed serum TSLP of 160.91 pg/mL, comparable to the mean TSLP in the 12 UD pSS-NHL (151.96 pg/mL). Importantly, in pSS-related NHL in stable remission, serum TSLP resulted undetectable (7/13) or detectable at very low levels (6/13) (mean 10.46, 0-38.5), and significantly lower than in benign pSS patients from the two cohorts (n=203, mean 31.48, 0-140.8; p=0.0022). Metachronous samples from one patient, at the stage of NHL activity and then at NHL remission, showed a decrease in TSLP from 128.04 pg/mL to undetectable levels. Finally, TSLP levels were increased also in the Greek cohort (mean 54.9, 26.72-78.95), and significantly higher than the two Italian cohorts (p=0.0085 and p<0.0001, vs cohort 1 and 2, respectively). Conclusion: Serum TSLP levels are increased in pSS, as herein confirmed in independent cohorts. TSLP might be important in the disease pathophysiology and mirrors the course of pSS-related B-cell lymphoproliferation itself. It may thus represent a novel important biomarker. References: [1]Gandolfo S. et al, Clin Exp Rheumatol. 2019 May-Jun;37 Suppl 118(3):55-64. Disclosure of Interests: Saviana Gandolfo: None declared, Cinzia Fabro: None declared, Serena Colafrancesco: None declared, Francesco Carubbi Speakers bureau: Francesco Carubbi received speaker honoraria from Abbvie and Celgene outside this work., Francesco Ferro: None declared, Elena Bartoloni Bocci: None declared, Efstathia Kapsogeorgou: None declared, Andreas Goules: None declared, Luca Quartuccio Consultant of: Abbvie, Bristol, Speakers bureau: Abbvie, Pfizer, Roberta Priori: None declared, Alessia Alunno: None declared, Guido Valesini: None declared, Roberto Giacomelli Grant/research support from: Actelion, Pfizer, Speakers bureau: Abbvie, Roche, Actelion, BMS, MSD, Ely Lilly, SOBI, Pfizer, Roberto Gerli: None declared, Chiara Baldini: None declared, Athanasios Tzioufas: None declared, Salvatore De Vita Consultant of: Roche, Human Genome Science, Glaxo Smith Kline and Novartis